Navigating Translation Accuracy: A Qualitative Study on EFL Students' Post-Editing Strategies of Google Translate Outputs - Annastasya Maulidatu Mutiarani (Gema Cendekia Institute, 2026)
Academic writing and translation assignments in the context of English as a Foreign Language (EFL) undergraduate programs are closely linked to the use of machine translation (MT) tools, particularly Google Translate (GT). Although its use has become widespread, the post-editing strategies employed by EFL students when revising GT translations have not yet been extensively explored in the Indonesian context. This qualitative study aims to investigate the post-editing strategies, metacognitive processes, and critical language awareness of EFL students at a university in Indonesia as they evaluate the accuracy of GT translations in academic translation assignments. Using a dynamic narrative inquiry approach supplemented by open-ended questionnaires and semi-structured interviews, this study involved five undergraduate EFL students from the English Language Education Program as participants. The data were analyzed thematically following Braun and Clarke’s (2006) six-phase framework and interpreted through the lens of metacognitive strategy theory and Communities of Practice. The findings revealed four main themes: (1) a variety of post-editing strategies, ranging from holistic reading to targeted lexical corrections; (2) awareness of the limitations of machine translation (MT) in academic registers and collocation accuracy; (3) the mediating role of English language proficiency in revision decision-making; and (4) critical translation competencies that are still limited but continue to develop. These findings have significant implications for translation pedagogy, EFL curriculum development, and the responsible integration of MT tools in higher education. This study underscores the need for explicit post-editing instruction and metacognitive awareness training in EFL translation courses